IC 9379 Coal Reserves Of The Boltsfork Quadrangle, Kentucky A Coal Recoverability Study - Timothy J. Rohrbacher (The National Institute for Occupational Safety and Health (NIOSH), 1994)
This report presents a U.S. Bureau of Mines study that incorporates coal mining factors, coal recovery factors, and economic factors into the definition of an economically recoverable coal resource. The relationship between these factors to the Energy Information Administration's estimate of U.S. coal resources-the "Demonstrated Reserve Base"-is discussed. The Boltsfork 7 1/2-minute quadrangle in eastern Kentucky was selected as the study area. Results indicate that of the original 280.2 M tons of resource in the quadrangle, only 99.8 M tons (35.6%) is recoverable at a mining cost of $25 per ton or less.